Management Of Continuing Professional Development On Madrasah Aliyah Negeri Teachers To Improve Pedagogic Competence - Elisa Roosmawati; Didin Wahidin; Hendi Suhendraya Muchtar; R. Supyan Sauri (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2022)
To support the success of teachers, pedagogic competencies are required to be developed and carried out in a sustainable manner. The problem of teachers in the Continuing Professional Development (CPD) effort is faced with various problems that do not only come from the teachers themselves but also from other factors such as policies. This study aimed to obtain information focused on 1) CPD planning to improve pedagogic competence of MAN teachers; 2) Organizing CPD to improve the pedagogic competence of MAN teachers; 3) Implementation of CPD to improve pedagogic competence of MAN teachers; 4) Evaluation of CPD to improve pedagogic competence of MAN teachers. This study used Terry & Rue's Management theory, and Spencer's Theory of Pedagogic Competence and Longman's theory of professionalism. This study used a qualitative approach with a case study method. The technique and instrument of data collection used triangulation method. The data sources used were triangulation of sources namely Head of Education Office, Principal of MAN, Teachers, and members of MGMP. Based on the results, 1) CPD planning has not been fully prepared by the madrasah and teachers. CPD planning is only planned when the teachers will arrange the administrative equipment for promotion, so that it cannot be used as an effort to improve the pedagogic competence of teachers. 2) Organizing CPD has been carried out through the CPD team organized by the madrasah, but in reality, the CPD Team has not been able to fully improve the pedagogic competence of teachers. Thus, the organization has not run effectively in accordance with the applicable guidelines regarding CPD. 3) The implementation of CPD is more directed at efforts to fulfill administrative tasks where teachers are still constrained in the preparation of innovation works, self-development activities and scientific publications; 4) CPD evaluation based on self-evaluation cannot be used as a basis for continuous improvement of CPD. CPD evaluation has not been considered as important for teachers in improving pedagogic competence. Thus, it can be concluded that the CPD to improve the pedagogic competence of MAN teachers has been implemented based on existing regulations and is running in accordance with the CPD program guidelines, but has not shown maximum efforts to improve the pedagogic competence of teachers.